Strategies and difficulties in translating Palestinian women's idioms into English among certified translators - Zayed, Mujahed Hossien Tahir (2023)
A considerable amount of research has been done on idiom translation, but most of the studies focus on amateur or non-professional translators consisting of undergraduate and postgraduate students. The present study focuses on the translation of Palestinian women’s idioms from Arabic into English by Palestinian certified translators. It aims to investigate the translation strategies employed by the translators when they translate women’s idioms and determine the appropriate strategies from those employed. Moreover, it aims to identify the difficulties encountered by Palestinian certified translators in translating Palestinian women’s idioms from Arabic into English along with the reasons behind the difficulties. The present study adopts a qualitative approach where two data collection instruments are employed. The data collection instruments are semi-structured interviews and a translation task. Thus, this study employed Baker's (2018) and Newmark's (1988) models as its theoretical framework. The data analysis showed that the Palestinian certified translators employed five translation strategies: paraphrasing, using a TL idiom with similar meaning but dissimilar form, literal translation, proverbialisation and omission. The strategies of Paraphrasing, using a TL idiom with similar meaning but dissimilar form and proverbialisation were proven appropriate to overcome the difficulties encountered when translating Palestinian women’s idioms from Arabic into English. The data analysis also revealed that proverbialisation, as a new strategy presented for the first time in this study, can be used to translate Palestinian women’s idioms from Arabic into English. Moreover, the analysis of the data revealed that the translators encountered some difficulties in translating Palestinian women’s idioms for a variety of reasons. The Palestinian certified translators faced cultural difficulties, linguistic difficulties, denotative difficulties and idiomatic difficulties in translating Palestinian women’s idioms from Arabic into English. The cultural difficulties were because Arabic and English belong to two different cultures, lack of cultural knowledge, having no equivalent idioms, the uniqueness of the Palestinian culture and that Palestinian women are a special case. The reasons which led to linguistic difficulties were grammatical variations, semantic variations and syntactic variations between Arabic and English. The denotative difficulties were faced because some Palestinian women’s idioms are obsolete or old, the sensitivity and complexity of women’s idioms and the fact that some Palestinian women’s idioms are used only in certain regions. The idiomatic difficulties were attributed to the ambiguity of some Palestinian women’s idioms. Thus, the findings of this study present taxonomy of the difficulties which may face translators in translating idioms from Arabic into English.